Aplastic Anemia Frequency and Management in Pediatric Liver Transplantations Due to Non-A-E Hepatitis - Kıran Taşcı, Ezgi; Karakoyun, Miray; Özdemir Karadaş, Nihal; Hekimci Özdemir, Hamiyet; Karapınar, Deniz Yılmaz; Karaca, Can; Çetin, Funda; Aydoğdu, Sema (Turkish Journal of Gastroenterology, 2021)
Background: Hepatitis-associated aplastic anemia (HAAA) is a rare complication that presented with bone marrow failure after acutehepatitis. HAAA usually occurs in adolescent men within 1-6 months following hepatitis. Most of HAAA’s etiology has non-A-E viralhepatitis.Methods: Our retrospective study included patients with acute fulminant hepatitis who had been treated in Ege University PediatricGastroenterology, Hepatology and Nutrition Department and İzmir Kent Hospital Clinical, laboratory, and epidemiological data of thepatients were collected from the files.Results: In this study, 499 children underwent liver transplantation (LT) in two pediatric transplantation centers. Sixty-eight (13.6%)out of 499 patients, underwent liver transplantation due to fulminant hepatic failure (FHF). Therefore, a total of 64 patients (34 girls,30 boys) with a diagnosis of FHF have included in the study. Thirty-two (50.0%) of 64 FHF were due to non-A-E hepatitis and 4 out of the64 patients (6.2%) with FHF developed HAAA. All of the patients received prednisolone as immunosuppression treatment after LT. Threepatients were also given Tacrolimus and 1 received an additional mycophenolate mofetil. One of the patients was given prednisoloneand cyclosporine treatment without tacrolimus. Bone marrow transplantation was performed in 1 patient (25.0%). Two of the patientsreceived immunosuppressive treatment including rabbit-derived anti-thymocyte globulin, cyclosporine, and initially prednisolone.Conclusion: In children who underwent liver transplantation for non-A-E FHF are at high risk to develop aplastic anemia. The cliniciansshould be alert after orthotropic liver transplantation patient could develop aplastic anemia and early treatment with immunosuppressivetherapies result in a more successful outcome.